Infections in type 2 diabetic patients and its correlations with glycosylated haemoglobin in a tertiary care teaching hospital - Mohapatra, Namita; Soreng, Pratima; Mohanty, Dibya Prasanna; Mohapatra, Gurukrushna (International Journal of Research in Medical Sciences, 2019)
Background: Diabetes mellitus increases the risk of infections and results in adverse outcomes, but the effect of better glycaemic control has not been thoroughly investigated. Therefore, it was intended to study the various types of infections in Type 2 diabetic patients and its correlation with HbA1c. Methods: It was a prospective observational study for one year, conducted on Type 2 diabetic patients hospitalized for various causes. Patients with HIV infection or immunocompromised state were excluded. Routine investigations, radiological and culture studies were conducted as required to identify the various infections present. The prevalence of infections was then corelated with blood glucose and HbA1c levels. Results: Total 105 hospitalized diabetic cases were studied, out of which infections were detected in 72 (68.6%) patients, which was found to be statistically significant. The most common infection detected was UTI (45.8%). Among the UTI patients, E. coli was the most common organism isolated (52.3%) followed by Enterococcus (19%), Pseudomonas (19%) and Citrobacter (9.5%). Infections occurred in 61 (82.4%) patients with HbA1C >6.5% and in 11 (35.5%) patients with HbA1C <6.5%, which was found to be statistically significant. Conclusions: Diabetes increases the risk of infections. Urinary tract infection is the most common infection, affecting the females predominantly. An association between current hyperglycaemia, glycosylated haemoglobin and infection risk in type 2 diabetes patients was found.